Gaṇitagannaḍi: A Karaṇa Text of 1604 CE on Siddhāntic Astronomy in Kannaḍa - Shylaja, B. S.; Javagal, Seetharam (History of Science in South Asia)

(untitled) (University of Alberta Library, 2020)
From a private collection of palm leaf manuscripts the text Gaṇitagannaḍi has been unearthed and studied. The contents follow the traditional texts with all the chapters starting from the calculation of ahargaṇas to the predictions of eclipses. The text presents a unique method of calculation which the author, Viddaṇācārya, declares to be his own invention. In this paper, the procedures are described with the help of the elaborate commentary, written in Kannaḍa language, by Śaṅkaranārāyaṇa Jōisaru of Shringeri This paper highlights the uniqueness of the procedure for calculating the ahargaṇa and the dhruvās for the positions of planets.